The diagnosis of malaria and identification of plasmodium species by polymerase chain reaction in Turkey - Aslan, Gonul; Seyrek, Adnan; Kocagoz, Tanil; Ulukanligil, Mustafa; Erguven, Sibel; Gunalp, Ayfer (Elsevier Ireland Ltd, 2007)
More than half of the world's population is exposed to malaria in approximately 100 countries. Rapid diagnosis and correct treatment of cases are the main objectives of control programs in malaria endemic areas. We have developed a PCR method to determine the presence of plasmodium DNA in blood. The method can also identify the species of the plasmodium by restriction enzyme analysis of the amplified product. We evaluated the performance of this method in the diagnosis of malaria suspected cases in Turkey by comparing to microscopy of the blood smears: blood samples were obtained from 114 patients with malaria symptoms, including fever and/or chills lasting for several days, before starting treatment. Thin and thick blood smears were prepared immediately in the region of specimen collection. After isolation of DNA from blood samples, DNA was amplified by PCR and digested by restriction enzyme AluI. The obtained fragments were analyzed by agarose gel electrophoresis. The number of parasites in the thick and thin smears of the blood samples was evaluated microscopically after staining by Giemsa and results were compared by PCR results. Among 114 plasmodium positive cases detected by microscopy, 100 were also detected by PCR. There were 14 false negatives and no false positive by PCR. Compared to microscopy, the sensitivity, specificity and Positive Predictive Value (PPV) of PCR were determined as 76%, 100% and 100%, respectively. (c) 2007 Elsevier Ireland Ltd. All rights reserved.
Keywords: malaria; Plasmodium vivax; Plasmodium falciparum; polymerase chain reaction